4 practice tests + proven strategies + online + audio (New York, 2017)
Provides strategies, tips, and four practice tests covering listening, reading, writing, and speaking skills and is thematically arranged by history, science, education, business, social science, arts, technology, and entertainment.
Keywords: Tiếng Anh,English language; Kỳ thi,Examinations